Website Based (We-Retag) as Chemical Foam Quality Tests Record on Foam Tender Vehicles - Andayani, Thursina -; Zuliano, Arief -; Rusmana, Ganda -; Wirawan, Yani Yudha (Universitas Dharma Wacana, 2025)
This study aims to design a We-ReTag website (we enter record tag) which digitally able to record the outcomes of foam quality testing on foam tender vehicles more efficiently than logbooks or spreadsheets. In addition, this study also ensures that the website is designed to be easy to use (user-friendly) for inputting data on foam quality test results. A material expert and an IT expert who serves as a We-ReTag website validator are the study's subjects. The entire 36 (thirty-six) ARFF personnel at Sultan Mahmud Badaruddin II Airport Palembang are the subject of this website's design. This study used a waterfall model in conjunction with the research and development (R&D) approach. Starting with the requirements stage, this process moves on to desing, implementation, testing, and verification before coming to an end with maintenances. Thes result of study show that We-Retag website was highly appropriate for usage in ARFF unit of SMB II airport based on validation from IT and material specialist with average scale of 87%. In addition, the average scale obtained from the questionnaire filled out by ARFF personnel was 89 %. The benefit of this research is to increase the effectiveness in chemical foam quality test record and expected its usage can be disseminated to other airport throughout Indonesia in similar operational context.